Cerebrovascular disease in COVID-19: Is there a higher risk of stroke? - Altable, Marcos; De la Serna Tuya, Juan Moisés (Brain, Behavior, and Immunity - Health, 2023)
The presence of stroke has been observed in young adults (under fifty years of age) without cardiovascular risk factors who are suffering from COVID-19. It is speculated that there is really a significant increase, as a few cases have yet to be described, or that the infection favors his development. Cerebrovascular events are more common in older patients with stroke risk factors, such as hypertension and diabetes mellitus, and those who have elevated fibrin D-dimers. Multiple case reports and series about cerebrovascular disease (CVD) in COVID-19 has been informed. The mechanism that causes cerebral ischemia in COVID-19 remains undiscovered. However, progressively there is increasing evidence of hypercoagulability that can be or contribute to the cause. We review the current literature about CVD both epidemiology and etiology. More studies are needed to understand.
Keywords: cerebrovascular disease; COVID-19; endothelitis; hipercoagulability; stroke; young; Scopus